Sudan : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1997)
This paper reviews economic developments in Sudan during 1992-96. Real GDP rose by 5.3 percent in 1992/93 when rains were good and by about 4.5 percent during 1993/94-1995/96, as an uneven pattern of rainfall produced swings in output. With the exception of the first half of 1995, the central government's fiscal performance was weak during 1992/93-1996, with expenditures typically twice as high as revenues and the deficit (on accrual basis) ranging between 18.7 percent of GDP in 1992/93 and 12.7 percent of GDP in 1994/95.